China’s Rise in a Changing World - Lanteigne, Marc; Koivurova, Timo; Nojonen, Matti (Brill Nijhoff, 2020)
As China’s cross-regional diplomacy is not separated from the party-state’s overall foreign policy goals and doctrines, this chapter offers a review of China’s foreign policy and economic interests. Without doubt, these dynamics also shape China’s policy in the Arctic. The chapter concludes that Beijing is no longer content to be a norm-taker in international politics but it is more comfortable with becoming a norm-maker. However, there are noteworthy differences between China’s Arctic engagement and its diplomacy in other parts of the world.